(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The amino acid composition of the roots of Harpagophytum procumbens was investigated by the method of high performance liquid chromatography (HPLC) with preliminary derivatization. Sixteen free and thirteen bound amino acids were quantitatively determined. The content of protein-bound amino acids was calculated. Dhaka Univ. J. Pharm. Sci. 18(1): 85-91, 2019 (June)